The Ag- And Au-bearing phases in the Escondida epithermal vein, Cerro Moro deposit, Santa Cruz, Argentina - Mugas Lobos, Ana Cecilia (2020)
The Cerro Moro deposit is located at 488505500S, 6683901.600W and 100 m.o.s.l. in Santa Cruz province, southern Argentina. It is a low sulfidation Au-Ag epithermal mineralization hosted by numerous NW-SE structurally controlled quartz veins developed in close spatial and temporal proximity to the products of Jurassic extension and magmatism. The Escondida vein is the most significant mineralized structure, as it hosts the base metal-rich and Au-Ag high grade mineralization. In this vein and the Zoe ore-shoot, ore minerals are abundant (sphalerite, galena, chalcopyrite, acanthite, and less abundant pyrite and marcasite) and frequently related to dark grey, fine-grained quartz with massive, porous, crustiform, and banded textures; variable quantities of fine-grained flakes of muscovite are locally present. The Ag- and Au-bearing mineral association is represented by acanthite, argyrodite, polybasite, pearceite, stromeyerite, mckinstryite, and jalpaite. Abundant acanthite occurs commonly associated with gold and silver; copper enrichments were detected and interpreted as nanoinclusions of Cu-bearing minerals. The occurrence of Se- and Te-enriched minerals (acanthite, argyrodite, polybasite, pearceite, stromeyerite, and mckinstryite), rather than silver selenides and/or tellurides, indicates the presence of reduced mineralizing fluids and may be ascribed to partial substitution of S by Se or Te. Polybasite and pearceite were differentiated by their chemistry. Although the presence of argyrodite in epithermal deposits with silver sulfosalts is relatively common, this first mention in Cerro Moro is highly encouraging for exploration for germanium, a critical element, which is also considered strategic by countries such as the USA and China.